(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
Steel P91 is widely used in power stations due to its goоd creep resistance and predictable performance. The aim of this work was to compare the toughness values of different zones in the weld joint with a sample subjected to a simulated thermal cycle. The workpieces were welded using Gas Tungsten Arc Welding (GTAW) for the root pass and Manual Metal Arc (MMA) for the filler deposition. Post Welding Heat Treatment (PWHT) was carried out at 740 °C for 2 hours. The welded joint was tested for microstructure, macrostructure, hardness, strength and toughness. The macrostructure showed all typical zones with a tempered martensite microstructure. The difference in the carbide distribution, which were confirmed by the hardness measurements, are the result of variations in the chemical composition. The tensile strength and the fracture which occurred in the base metal, indicate good properties of the welded joint. The crack initiation energies determined were similar in the Base Metal (BM), Heat-Affected Zone (HAZ), and Weld Metal (WM), while the crack propagation energy was lowest in the WM. This indicates that carbides control the crack initiation energy, while their distribution influences the crack propagation. The simulated HAZ samples showed lower toughness compared to the welded specimens, which can be attributed to the differences in the performed thermal cycles. During welding, the HAZ undergoes several thermal cycles in each pass, resulting in smaller austenitic grains compared to the simulated HAZ. Lower values of toughness indicate that the simulation provides a conservative approach, i.e. the measured toughness is lower than the toughness in a real welded butt.